MELAKSANAKAN SUPERVISI AKADEMIS MELALUI PENELITIAN TINDAKAN SEKOLAH (SCHOOL ACTION RESEARCH) - Aan Komariah (Universitas Pendidikan Indonesia, 2009)
Educational Supervision is intended for the improvement and development of the quality general education and the learning process in particular. Academic supervision is directed at teachers establishment so they can show the best performance and professional behavior in performing learning teaching process. The Effective of supervision should be based on competence, commitment and motivation of supervisors and implemented in a planned, directed and sustained through an approach to clinical supervision in school action research (SAR) frame. SAR is believed to increase the cafacity and cafability supervisee and supervisors through the implementation of the supervision activities that go from self-reflection to solve the problem of leaching learning.